Diction problems among voice students in singin foreign languages: The importance of diction class in UiTM / Dayang Syarfa Syazana Datu Shadan - Datu Shadan, Dayang Syarfa Syazana (2013)
This study will look at the importance of IPA and how diction class can solve the diction problems among voice students in the Faculty of Music, UiTM, Shah Alam. The purpose of this study was to find out the diction problems among voice students in singing foreign languages and the importance of diction class, also the student's perceptions on the importance of learning diction in singing foreign language. This study involving 30 voice students in the Faculty of Music, UiTM, Shah Alam. From the findings, the result can be obtained from the questionnaire that has been distributed.